2019
DOI: 10.14701/ahbps.2019.23.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Utility of liver function tests in acute cholecystitis

Abstract: Backgrounds/Aims Common bile duct stones (CBDS) affect the management of acute cholecystitis (AC). This study aims to investigate the utility of liver function tests (LFTs) in predicting the presence of CBDS in AC patients. Methods Retrospective cohort study of adult patients with AC found in the American College of Surgeons National Surgical Quality Improvement Program database from 2008 to 2016. Patients were classified into two groups, without CBDS (AC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 32 publications
(49 reference statements)
2
25
0
Order By: Relevance
“…Hemolysis is the most common cause of indirect hyperbilirubinemia followed by Gilbert’s syndrome. On the other hand, direct hyperbilirubinemia indicates liver pathology including cholestatic drug reactions, autoimmune cholestatic disease, and biliary obstruction[ 21 ].…”
Section: Pattern Recognition and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemolysis is the most common cause of indirect hyperbilirubinemia followed by Gilbert’s syndrome. On the other hand, direct hyperbilirubinemia indicates liver pathology including cholestatic drug reactions, autoimmune cholestatic disease, and biliary obstruction[ 21 ].…”
Section: Pattern Recognition and Interpretationmentioning
confidence: 99%
“…Acute cholecystitis (AC) usually presents as a cholestatic pattern or mixed. The biochemical test abnormalities are associated with obstruction from CBD, reactive hepatitis, fatty liver, direct gallbladder pressure on the biliary tract, or portal tract inflammation[ 19 - 21 ]. Patients with calculous AC may have CBD stones in up to 15%[ 17 ].…”
Section: Common Conditions Associated With Abnormal Liver Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in certain diseases, such as hemolytic anemia, hepatic jaundice, and biliary disease, the serum bilirubin level is greatly elevated and leads to the excessive production of urobilinogen. Thus, a positive result shows in the urinalysis 18,19 . However, our study demonstrated that most of the AHP patients showed normal serum bilirubin levels, consistent with the literature 9,15,20−22 .…”
Section: Discussionmentioning
confidence: 91%
“…However, in certain diseases, such as hemolytic anemia, hepatic jaundice, and biliary disease, the serum bilirubin level is greatly elevated and leads to the excessive production of urobilinogen. Thus, a positive result shows in the urinalysis (10,11). So we believed that using serum total bilirubin for calibration could help the doctors to identify the false-positive urinary urobilinogen and furthmore suspect the diagnosis of AHP.…”
Section: Introductionmentioning
confidence: 99%